The Effect Of Some Media Lumpur Lapindo Proportions With The Soil And Dosage Of Organic Fertilizer On The Growth Beginning Of Plant Banana King (Musa Paradisiaca L.) - Sri Kusuma Wardani; Abdul Wachid (Universitas Muhammadiyah Sidoarjo, 2016)
The research objective was to determine the effect of the proportion of Lapindo mud and the addition of organic fertilizer to the growth of banana plant seeds. Factorial research using randomized block design (RBD) was repeated three times. The first factor is the proportion of Lapindo mud, which consists of four levels, namely 100% ordinary land (land not contaminated with Lapindo mud), 20% Lapindo mud: 80% ordinary land, 40% Lapindo mud: 60% ordinary land, 60% mud lapindo: 40% of ordinary land. The second factor is the use of organic fertilizer which consists of three levels, namely not using 500 grams of organic fertilizer 750 grams of organic fertilizer Organic fertilizer. The observed characters were stem diameter, plant length, number of leaves, plant wet weight and plant dry weight. Data analysis using 5% ANOVA continued with BNJ test. The results showed that the more content or mixture of Lapindo mud mud the banana plant growth was getting worse. Giving Lapindo mud mixture range of 20%, namely in the ratio of 3 kg Lapindo mud with 12 kg of ordinary land. With the addition of 50% to 75% organic fertilizer improves the growth of banana plants.